1978
DOI: 10.1037/h0081683
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the saliency of sensory features elicited by words.

Abstract: This research is based upon a thesis submitted in partial fulfilment of the requirement for the doctoral degree at the University of Western Ontario. The suggestions, criticisms, and support for this project given by his committee members, DrsJ.P. Denny, R.C. Gardner, L. Prytulak, and J. Siegel, are gratefully acknowledged. Dr. D.J. Herrmann, in a most useful review, provided many suggestions incorporated in this paper. A special thanks is due to my research supervisor, Dr Allan Paivio, for the many ways in wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Property Goodness: Typicality (Tl) Rosch (1975) has shown that some instances are considered to be better or more typical of a category than are others. Katz (1978) has shown that properties of items can be similarly scaled. In the present task, Rosch's (1975) scaling procedure was employed.…”
Section: Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Property Goodness: Typicality (Tl) Rosch (1975) has shown that some instances are considered to be better or more typical of a category than are others. Katz (1978) has shown that properties of items can be similarly scaled. In the present task, Rosch's (1975) scaling procedure was employed.…”
Section: Techniquementioning
confidence: 99%
“…Finally, the norms should prove useful in studies of concept identification. Dominance (Underwood & Richardson, 1956b), typicality (Katz, 1978), rank (Mednick & Halpern, 1962), and the ratio of relevant to irrelevant properties (Underwood, 1957) are variables already shown to be of importance in the identification literature, and each is present or easily computed from the sets of norms given here. struct (e.g., goodness) does not correlate too highly with a measure of a conceptually distinct construct (e.g., dominance).…”
Section: Variablementioning
confidence: 99%